Efek pemberian ekstrak klorofil daun pepaya (carica papaya, linn.) terhadap kadar ast dan alt serum - Damayanti, Kusmadewi Eka; Wijayahadi, Noor; Puruhita, Niken (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2015)
Background: Pharmacological therapy is one of the therapy modalities which carries the hepatic injury as one of its side effects. Nowadays, curcuma tablets has become choice of hepatoprotector. Other substance which has the possibilities of hepatoprotection activities is chlorophyll. The study is aimed to investigate the effect of papaya leaves chlorophyll extracts towards the serum AST and serum ALT levels on high-dose-paracetamol-induced Wistar rats. Materials and methods: This was an experimental study applying pretest-posttest controlled group design. Twenty eight Wistar rats 8-12 weeks age and weighted 185-220 grams assigned into four groups, namely group I (control), group II (paracetamol 750 mg/kg bw + no hepatoprotector agent), group III (paracetamol 750 mg/kg bw + curcuma 100 mg/kg bw), and group IV (paracetamol 750 mg/kg bw + papaya leaves chlorophyll extracts 300 mg/kg bw). The hepatoprotector agents were administered for a week, while the high dose paracetamol was administered for three consecutive days (day 5, 6, and 7). The pretest samples were drawn on the fifth day before the administration of high dose paracetamol, and the posttest samples were drawn on eightth day. Results: There were no difference among four groups on serum AST and serum ALT levels before the administration of high dose paracetamol, p=0.522 dan p=0.682, respectively. After the administration of high dose paracetamol, there were differences among four groups on both variables, both p=0.000. The post-hoc test showed that differences happened on all four groups (p<0.05).Conclusion: Chlorophyll extract of papaya leaves can inhibit liver injury on high-dose-paracetamol-induced-Wistar rats.Â